Echocardiographic comparison between pulmonary valve preservation and transannular patch techniques in children with repaired Tetralogy of Fallot. (8th February 2021) - Avesani, M; Guariento, A; Schiena, CA; Reffo, E; Castaldi, B; Padalino, M; Vida, V; Di Salvo, G
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Many centers have recently adopted pulmonary valve (PV) preservation procedures to prevent the detrimental long-term effects of chronic pulmonary regurgitation after tetralogy of Fallot (ToF) repair. PURPOSE: The aim of our study was to investigate pulmonary valve (PV) and right ventricular function by echocardiography in paediatric patients with repaired Tetralogy of Fallot (ToF), comparing PV preservation surgical strategies to standard transannular patch (TAP) repair. METHODS: All patients undergoing transatrial-transpulmonary repair for ToF at our institution between January 2007 and May 2020 were reviewed retrospectively. Patients were divided into 2 main groups, according to the different techniques used: patients undergoing a PV preservation strategy and patients undergoing TAP repair. All patients underwent standard echo-Doppler study including RV end-diastolic area (RVEDA), end-systolic area (RVESA), fractional area change (FAC) and TAPSE; PR was assessed by Color Doppler, continuous-wave (CW) Doppler and derived parameters such as pressure half time (PHT) and pulmonary regurgitation (PR) index. By speckle tracking we measured also, in a subgroup of patients, right atrial strain (RAS), RV and left ventricle (LV) global longitudinal strain (RVGLS, LVGLS) and their time to peak (TTP) values. RESULTS: Overall, 82 patients underwent a successful PV preservation strategy while 34 underwent a standard TAP repair. At index surgery, BSA (0.31 ± 0.1 m2, P = 0.3), age (4.8 ± 0.3 months, P = 0.5) and preoperative PV Z-score (-3.20 ± 0.1, P = 0.1) did not different between groups. Five-year actuarial freedom from moderate/severe PV regurgitation was significantly higher in the PV preservation group compared to the TAP (61.3% [95% CI: 48-73%] vs 25.9% [95% CI: 12-43%], respectively; p = 0.02). After adjusting for age, gender, BSA, and type of PV, the use of a TAP was still significantly associated with an increased risk for PV regurgitation at follow up (HR: 1.85, 95% CI: 1.09, 3.15; p = 0.02). At a mean follow-up of 6.9 ± 0.3 years, patients undergoing PV preservation showed an increased right ventricular fractional area change (46.9 ± 0.8% vs 42.5 ± 1.7%, P < 0.001) and tricuspid annular plane systolic excursion (TAPSE) z-score (-3.36 ± 0.3% vs -4.7 ± 0.4%, P = 0.005), while maintaining better PV competence in terms of pulmonary regurgitation index (87.9 ± 1.2% vs 82.7 ± 2.4%, P = 0.02). At speckle tracking subanalysis, patients undergoing PV preservation (n= 23), compared to the TAP group (n = 13) showed also higher values of RAS (37.5 ± 6.0% vs 29.3 ± 8.2%, P < 0.006), shorter right TTP (319 ± 39ms vs 357.5 ± 45.2 ms, P < 0.01) and higher values of LVGLS (-20, 6 ± 4, 2% vs -17.5 ± 3.0, P < 0.03). CONCLUSIONS: Surgical repair of ToF with PV preservation provides excellent outcomes in terms of PV competence and right ventricular function and should be advocated whenever possible.